A Corpus Based Analysis of Adjectives Adorable, Charming, and Cute in Corpus Contemporary American English (COCA) - Ramayanti, Ni Putu Desi; Sukarini, Ni Wayan; Weddha Savitri, Putu (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 22 No 1 (2022), 2022)
In order to avoid misunderstanding in the process of communication, knowing well the meaning of a word is important. Especially, when the two or three words share similar meaning and often used interchangeably in the sentences such as the adjectives word; adorable, charming, and cute. Therefore, this study aimed to find and to analyse the collocative meaning of the three adjectives. In this study, the data were collected from Corpus of Contemporary American English (COCA) by applying the documentation method with the note-taking technique. This study used a corpus-based analysis, with the help of the theory of collocative meaning and supported theory of lexical collocation were applied. The result showed that the collocative meaning of the three adjectives share similar meanings which collocated with the word attractive . Moreover, the three adjectives were most likely to co-occur with nouns such as; baby, guy, boys, and etc. The three adjectives were also commonly paired up with adverbs such as; quite, so, always and etc.